2017
DOI: 10.1002/srin.201700303
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Alkali Flow in Ironmaking Reactors by a Thermochemical Approach: Blast Furnace

Abstract: Elements like potassium and sodium have a negative impact on the blast furnace performance. Therefore, the flow of alkali metals in and out of the reactor has to be controlled. In the furnace, the chemical and physical properties of K and Na lead to the formation of a circulating movement. To point out the characteristics of this alkali-cycle, a thermochemical model is developed. The program is linked with the databases of Factsage 7.0. Based on a defined standard process, the alkali distribution in particular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Alike to Zn, K forms an inner circulation process in the blast furnace . Pichler et al set up a model describing the behavior of alkalis in the blast furnace They observed that the highest alkali load can be found in the middle of the blast furnace height, at temperatures between 923 and 1323 K. This area is in the same height of the blast furnace in which we detected the highest concentrations for the lining material (see Figure ).…”
Section: Resultsmentioning
confidence: 52%
“…Alike to Zn, K forms an inner circulation process in the blast furnace . Pichler et al set up a model describing the behavior of alkalis in the blast furnace They observed that the highest alkali load can be found in the middle of the blast furnace height, at temperatures between 923 and 1323 K. This area is in the same height of the blast furnace in which we detected the highest concentrations for the lining material (see Figure ).…”
Section: Resultsmentioning
confidence: 52%
“…As shown in Equation (1), K can continue to react to form KAlSiO 4 , resulting in a volume expansion of 39%, which is similar to the 36% volume expansion in Anton Pichler. [ 19 ] Therefore, the occurrence of reactions 1, 2, 5, 6, and 8 will cause volume expansion and destroy the carbon brick structure. In the erosion of harmful elements in blast furnaces, leucite (KAlSi 2 O 6 ) and sodium‐nepheline (NaAlSiO 4 ) are often found in carbon bricks, so the local volume expansion degree is calculated by this method to be 44% and 45%.2normalK(l)+Cl2(g)=2KCl$$2 \text{K} \left(\right.…”
Section: Resultsmentioning
confidence: 99%
“…The generation of new phases caused the volume expansion of the carbon brick. Previous studies have shown that the transformation from liquid potassium to kalsilite is accompanied by a volume expansion of about 36%, [ 22,24 ] which provides more favorable conditions for the generation of cracks and formation of the brittle zone.2K(l)+CO(g)+3Al2normalO3·2SiO2(s)=2KAlSiO4(s)+2Al2normalO3+C(s)…”
Section: Resultsmentioning
confidence: 99%